Fabrication of Silver Nanoparticles Using a Gas Phase Nanocluster Device and Preliminary Biological Uses - Oyarzun-Medina, S (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Nanoparticles can be used in a large variety of applications, including magnetic sensing, biological, superconductivity, tissue engineering, and other fields. In this study, we explore the fabrication of gas phase silver nanoparticles using a sputtering evaporation source. This setup composed of a dual magnetron cluster source holds several advantages over other techniques. The system has independent control over the cluster concentration and a wide range of cluster size and materials that can be used for the clusters and for the matrix where it can be embedded. Characterization of these silver nanoparticles was done using transmission electron microscopy (TEM). We obtain a lateral width of 10.6 nm with a dispersion of 0.24 nm. With atomic force microscopy (AFM) a Gaussian fit of this distribution yields and average height of 6.3 nm with a standard deviation of 1.4 nm. We confirm that the deposited silver nanoparticles have a homogenous area distribution, that they have a defined shape and size distribution, and that they are single standing nanoparticles. Given that the scientific literature is not precise regarding the toxic concentration of the nanoparticles, devices such as ours can help clarify these questions. In order to explore further biological applications, we have done preliminary experiments of cell spreading (myoblast adhesion), obtaining interesting morphological changes correlated with the silver concentration on the surface. With a deposited silver concentration ranging from 100-620 ng/cm 2 , the cells showed morphological changes in a short time of 2 h. We conclude that this high precision nanoparticle fabrication technique is adequate for further biological research. © 2018 by the authors.